Bibliometric Overview of Youth Empowerment in Social Science Research - Judijanto, Loso (The Eastasouth Journal of Social Science and Humanities, 2025)
This study presents a bibliometric overview of youth empowerment research within the social sciences, employing VOSviewer to analyze patterns of authorship, international collaboration, and thematic evolution from 2000 to 2024. A dataset retrieved from Scopus formed the basis for co-authorship, keyword co-occurrence, and temporal trend mapping. The analysis reveals Zimmerman M.A. as a central figure in the research network and the United States as the most prolific contributor, with notable partnerships involving countries such as Australia, South Africa, and Kenya. Thematically, the field has transitioned from early emphases on health education and risk prevention toward more contemporary focuses on mental health, leadership, and social justice. Keyword clustering illustrates the interdisciplinary nature of the field, integrating psychological, educational, health, and civic engagement frameworks. Temporal visualizations show a shift in conceptual priorities over time, while density mapping indicates core and peripheral research areas. The study highlights the importance of context-sensitive, inclusive, and forward-looking approaches to youth empowerment and identifies gaps for future investigation, particularly in areas such as digital inclusion and economic agency.